Bibliometric analysis of risk management in seaports - Ayman Nagi; Marius Indorf; Wolfgang Kersten (Digitalization in Supply Chain Management and Logistics: Smart and Digital Solutions for an Industry 4.0 Environment. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 23, 2017)
Seaports play an essential role in global supply chains. Incidents and accidents in such ports may lead to service delays, port closure as well as damage to people, property and the environment. Therefore, risk management in seaports plays an important role in mitigating and preventing possible accidents and disruptions. This paper aims to explore the structure of literature on risk management in seaports using co-citation analysis in order to reveal its current main research areas and gaps as well as its future trends. Document co-citation analysis is performed using the organization risk analyzer (ORA) software based on a specific threshold and employing the CoCit-Score method of calculation. Suggested future research areas on risk assessment and management methods as well as cooperative risk management are revealed based on the results of the co-citation analysis.
urn:nbn:de:gbv:830-88217601; 10419/209192; https://econpapers.repec.org/RePEc:zbw:hiclpr:23
Keywords: 650; risk management; seaports; co-citation analysis; supply chain risk management